PENINGKATAN KETERAMPILAN MENULIS SISWA DENGAN METODE QUANTUM LEARNING - yunisa oktavia (BASIS (Bahasa dan Sastra Inggris), 2016)
This research aims to describe the process and analyze thescore result of learning the review text with quantum learning method in class VIII-3 at SMPN 20 Batam. In essence, the research aims to improve the learning process of writing a reviewtext. Furthermore, by providing a quantum learning method can improve students' test scores in writing a reviewtext. This research is a classroom action research that use descriptive method. The research data is described qualitatively by observation checklist, field notes, questionnaires, and interviews. Data of learning outcome obtained from tests of writing reviewtext. This research was conducted in two cycles through four procedures: (1) planning, (2) actions, (3) observation, and (4) reflection. Based on the analysis of research finding, it can be summarized as follows;First, the learningprocess of writing the review text by using quantum learning method in class VIII-3 SMPN 20 Batam performed well in Cycle II. Second, the application of quantum learning method in writing a reviewtext in class VIII-3 SMPN20 Batam can improve the scoreof learning outcomes in writing reviewtext. The improvement was seen from the average count at each cycle, for example pra-cycles 58.72, 70.69 Cycle I and Cycle II 83.25.